Topical Oxybutynin 3% Gel versus Aluminum Chloride 15% Lotion in Treatment of Primary Focal Hyperhidrosis - El-Agamy El-Samadony, Amany; Salah Hegab, Doaa; Mohamed El Maghraby, Gamal; Hamed El-Maadawy, Iman (Dermatology Practical & Conceptual, 2023)
Introduction: Hyperhidrosis is excessive sweating beyond thermoregulatory needs. It is a potentially disabling condition with challenging management. Aluminum chloride is the established topical treatment; however, response remains unsatisfactory. Oxybutynin is an anticholinergic drug that stands as a therapeutic chance for hyperhidrosis. Objectives: comparing the efficacy of topical oxybutynin 3% gel versus aluminum chloride 15% lotion in treatment of primary focal hyperhidrosis. Methods: Forty patients with hyperhidrosis were randomly distributed into 2 equal groups treated by either topical oxybutynin 3% gel or topical aluminum chloride 15% lotion once daily night application for 4 weeks (both groups). Evaluation was done at 2 and 4 weeks of treatment and after 1 month of the end of treatment for follow up by Minor iodine starch test, hyperhidrosis disease severity scale (HDSS) and dermatology life quality index (DLQI). Results: Both treatment modalities were effective with insignificant differences between patients of both groups regarding improvement in Minor iodine starch test and HDSS after 2 weeks of treatment (P = 0.561, 0.33 respectively). Oxybutynin 3% gel yielded significantly better improvement of Minor’s test, HDSS and patient’s quality of life at the end of 4 weeks of treatment with lower recurrence rate than aluminum chloride 15% lotion at 1 month follow up. Minimal adverse effects were noted in both studied groups. Conclusions: Oxybutynin 3% gel could be considered as a promising treatment modality for hyperhidrosis with higher efficacy than aluminum chloride 15% lotion and lower recurrence rate.